Peningkatan Sanitasi Masjid di Kelurahan Mata Air Kota Padang Tahun 2022 - Trisfa Augia; Alicia Zulviarina; Husna Amalia; Indri Yulia Risha; Muhammad David Ewaldo; Nadifah Khairini Fahdi; Salsabila Zartin (Warta Pengabdian Andalas, 2023)
The mosque is one of the most visited public places. Currently, the sanitary conditions of the mosque are still not a concern of the community. There are still mosques that do not meet the sanitation requirements of public places. Poor mosque sanitation can cause various diseases in society caused by a polluted environment. This dedication aimed to present an overview of the sanitation condition of mosques in Mata Air, increase knowledge, and increase public awareness of the importance of mosque sanitation. The method used was data collection with sanitation inspection forms and personal hygiene questionnaires, interviews, dissemination of information through focus group discussion, and administration of the intervention of the book of pocket guides, poster, sanitary mosque SOPs, and garbage disposal in the Masjid of the Mata Air Village. The results of the sanitation assessment found that four of the eight mosques still have not met the sanitation requirements. Through this community dedication, an increase in the knowledge and awareness of mosque administrators regarding improving mosque sanitation was obtained. In this case, improved sanitation is essential to avoid the potential for disease transmission due to environmental pollution.